Promoting sustainable practices through energy engineering and asset management - Gonzalez-Prida, Vicente, 1975-; Raman, Anthony, 1968- (Advances in environmental engineering and green technologies (AEEGT) book series., 2015)
"This discusses the challenges that the developing world faces when implementing and utilizing environmentally friendly techniques for the adoption of sustainable practices in developing countries"--